Rancang Bangun Aplikasi Pengendalian Dokumen Sertifikat Kapal Berbasis Web Pada PT. Rukina Sukses Abadi - Hidayat, rizal nur; Sutanto, Teguh; Shintawati, Rahayu Arya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: Rukina Sukses Abadi Ltd work in dredging ocean base and reclamation sector. The company exist document control management as checking expired date for their dredger certificate. While the operator in the office belated certificate extension, that will have impact for dredger performance, because the dredger activity will waiting after certificate extension has been done, so the company has financial loss because the dredger doesn’t work.Based on the problem, made one application to solve dredger certificate document management as web basic. The system exist form input certificate document and certificate document management features, it showing notification when the certificate come on expired date, so it will resolved certificate extension time which impact to dredger activity.Conclusion of the trial, application of documents management it work to manage certificate, show warning notification of certificate come on expired date and give certificate report in the moments. Keywords: Applications, Warning, Document Certificate